2008
DOI: 10.1074/jbc.m800153200
|View full text |Cite
|
Sign up to set email alerts
|

Single-stranded DNA-binding Protein in Vitro Eliminates the Orientation-dependent Impediment to Polymerase Passage on CAG/CTG Repeats

Abstract: Small insertions and deletions of trinucleotide repeats (TNRs) can occur by polymerase slippage and hairpin formation on either template or newly synthesized strands during replication. Although not predicted by a slippage model, deletions occur preferentially when 5-CTG is in the lagging strand template and are highly favored over insertion events in rapidly replicating cells. The mechanism for the deletion bias and the orientation dependence of TNR instability is poorly understood. We report here that there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 42 publications
5
34
0
Order By: Relevance
“…The impediment occurs only on the leading strand because SSB protein eliminates the impediment on both sequences [60]. This outcome indicates that the instability would be driven on the leading strand, consistent with the observation that instability is greater when 5'CTG is in the lagging strand.…”
Section: Potential Mechanisms By Which Mmr Might Cause Cag Expansionsupporting
confidence: 73%
See 3 more Smart Citations
“…The impediment occurs only on the leading strand because SSB protein eliminates the impediment on both sequences [60]. This outcome indicates that the instability would be driven on the leading strand, consistent with the observation that instability is greater when 5'CTG is in the lagging strand.…”
Section: Potential Mechanisms By Which Mmr Might Cause Cag Expansionsupporting
confidence: 73%
“…If some aspect of the lagging strand configuration promotes slippage, there is no compelling explanation for why it should be limited to the template strand. Recent in vitro experiments have provided, however, at least one explanation [60].…”
Section: Potential Mechanisms By Which Mmr Might Cause Cag Expansionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work using CAG and CTG sequences containing 10 repeats has shown that these sequences form stable hairpins; moreover, it is known that these complementary sequences can also form duplex (11)(12)(13). However, the mechanism by which the complementary hairpins interact to convert to duplex has not been established.…”
Section: Discussionmentioning
confidence: 95%